The creeping influence of consultants on cities: McKinsey's involvement in Berlin's urban economic and social policies. Issue 91 (May 2018) - Vogelpohl, Anne; Klemp, Felicitas
Highlights: Expert influence on policies is creeping towards becoming a matter of course. Consultants exert their influence through organising consensuses and networks. Management consultants embed neoliberal logic into conventions of urban development. The growth consensus is stabilised through focusing on questions of 'how' and 'who'. Progressively deeper personal networks enable the unquestionability of consulting. Abstract: The involvement of management consultants in contemporary urban policymaking exemplifies how experts exercise political influence. In Berlin, the McKinsey consultancy has gained a particularly powerful role in shaping strategies in economic, but also social, issues. We examine two instances of its involvement from two different angles: Berlin 2020, a pro bono study by McKinsey that gives advice for a stronger economic dynamism, provides insights into how the consultancy establishes itself as a powerful actor in urban policymaking through stabilising the consensus on economic growth as a key goal for urban development; and the parliamentary debates on McKinsey's support for the city's integration plans reveal both intensified personal private–public networks and their political contestation. Both examples are thoroughly analysed by applying the documentary method. The entrepreneurial experts' political influence indicates a combination of neoliberalisation, market regulation, urban crises, and a demand for fast policies. We expose consultants' general tactics in contemporary policymaking and conceive these as a creeping expert influence on cities through organising consensuses and networks. We identify the processes of expert-driven local decision-making as mechanisms of concentrating urban political powers that are simultaneously endorsed and contested.